Sexual Behaviors After PrEP Discontinuation Among HIV Serodiscordant Couples in Kenya and Uganda. (1st October 2020) - Stalter, Randy; Mugwanya, Kenneth; Thomas, Katherine; Donnell, Deborah; Mujugira, Andrew; Ngure, Kenneth; Celum, Connie; Kidoguchi, Lara; Bukusi, Elizabeth; Baeten, Jared; Heffron, Renee
Abstract : Background: A strategy of pre-exposure prophylaxis (PrEP) transitioning to treatment as prevention is highly efficacious and cost effective for prevention of HIV transmission within HIV serodiscordant couples. We assessed whether couples who adopted this strategy experienced changes in sexual behaviors after HIV-negative partners discontinued PrEP and transitioned to rely primarily on their partner's adherence to antiretroviral therapy (ART) for prevention. Setting: Kenya and Uganda. Methods: Data are from the Partners Demonstration Project, a prospective, open-label evaluation of PrEP and ART use for HIV prevention. Using zero-inflated negative binomial models, we assessed changes in the level (ie, intercept) and trend over time (ie, slope) in total and condomless sex acts reported after PrEP discontinuation by HIV-negative partners. We conducted subgroup analyses based on HIV-negative partners' age and sex. Results: We included 567 couples where the HIV-negative partner discontinued PrEP because of their partner with HIV using ART for ≥6 months. HIV-negative partners were women in 32.6% of couples and had a median age of 30 years. We observed no change in the level or trend over time in total sex acts [level adjusted rate ratio (aRR) = 0.95, 95% confidence interval (CI): 0.87 to 1.04; trend aRR = 1.00, 95% CI: 0.99 to 1.01] or condomless sex acts (level aRR = 0.97, 95% CI: 0.81 to 1.17; trend aRR = 1.00, 95% CI: 0.98 to 1.03) reported after PrEP discontinuation versus prediscontinuation. No significant changes in behaviors were observed in age and sex subgroups. Conclusions: PrEP discontinuation seems to result in no significant changes in couples' sexual behaviors. These data further support a strategy of time-limited PrEP use by serodiscordant couples. Abstract : Supplemental Digital Content is Available in the Text.